THE IMPACT OF ADDING RAPHANUS SATIVUS SEEDS TO THE DIET OF BROILER BREEDERS ON EGG PRODUCTION AND QUALITY, HATCHABILITY, AND PHYSIOLOGICAL TRAITS - S. M. Abdulateef; Z. J. M. Saed; Dr.Thafer Mohammed; A. B. Mohammed (مجلة الأنبار للعلوم الزراعية)
Enhancing the productivity and welfare of broiler breeders is a major challenge in poultry, as fertility, egg quality, and hatchability are mainly determined by nutrition and physiological conditions. The aim of this study was to determine the effect of adding radish (Raphanus sativus) seeds and vitamin E to the diets of broiler breeders (Ross 308) on their physiological and other vital traits. A total of 200 chickens including 20 roosters were used in five treatments comprising T1 (control), T2 (vitamin E 300 mg/kg), T3 (radish seeds 4 g/kg), T4 (radish seeds 6 g/kg), and T5 (radish seeds 8 g/kg). The T4 treatment was more effective than the cellular therapies producing better egg weight and hatchability. The data showed lowered cholesterol and LDL levels and higher HDL levels along with improved liver enzymes (ALT & AST) highlighting the functioning of tissues and organs and the overall health of the chickens. This reduction in oxidative stress, maintenance of hormonal balance, and improved nutrient absorption was due to the antioxidants in the radish seeds and vitamin E. Such additives improve eggshell quality and hatching and embryonic development in poultry which makes them a safe and eco-friendly alternative for improving poultry performance and wellbeing. This study contributes towards sustainable agriculture practices in providing natural solutions for better consumer safety and food security by increasing production efficiency, improving food product quality, and reducing adverse environmental effects